Demographic profile and clinical spectrum of gallstone disease in a rural tertiary care center: A retrospective observational study - Ajender Singh,; Mukesh Kumar,; Sanjeev Singla,; Pushpendra Malik,; Chanderbhan, (Asian Journal of Medical Sciences, 2024)
Background: Gallstone disease is a major public health problem worldwide irrespective of age. The incidence of gallstone disease shows considerable geographical and regional variations. Aims and Objectives: The aim and objectives are to study the correlation between demographic profile and clinical spectrum of gallstone disease and to study the clinical spectrum of gallstone disease at a rural tertiary care hospital to assess the demographic profile of gallstone disease patients. Material and Methods: The present retrospective observational study was conducted in the Department of General Surgery, BPS Medical College for Women, Khanpur Kalan, District, Sonipat. A total of 342 patients with gallbladder disease were included. Results: Out of 342 patients, 294 were female and 48 were male. The most common presenting symptoms among gallstone diseases were right hypochondrium pain in 307 (89.8%) patients, followed by epigastric pain in 24 (7%) patients, and nausea in 11 (3.2%). Ultrasonography suggests that the highest number of patients were associated with multiple gallstones in 203 (59%) patients out of which 170 were females and 33 were males; single stones were associated with 139 (40.6%) patients out of which 124 were females and 15 were male followed by double calculi in 5 (1.5%) patients. Conclusion: Gallbladder stone disease is more common in females. It can affect any age group. The maximum number of gallstone disease patients present with pain in the right hypochondrium and nausea. Maximum patients had multiple calculi gallbladder disease. Gallstone disease with chronic symptoms affects the liver function and anatomy of the Calot’s triangle that may affect the surgical procedure outcomes and hospital stay.